SASTRA LISAN SUNDA SEBAGAI MEDIA JEJARING MOTIF UNTUK PENGUATAN NKRI (Sundanese Oral Literature as Media of Motifs Network for Strengthening the Unitty of the Republic of Indonesia) - Supriatin, Yeni Mulyani (Balai Bahasa Sumatra Barat, 2015)
AbstractDiversity and similarity of the motif found in oral literature in the archipelago can actually be adhesive for disintergration in the nation and it can strengthen the Homeland. The issues of regional programs, such as Malay and regional autonomy is one of the “threat” of the split nation. This study aimed to describe Sundanese oral literary motifs (as a baseline for comparison with other areas of oral literary motifs) that can be used as the media of motifs network for strengthening the nation. Analyzing data motif index approach. Source of data used are oral literature from Sunda belonging to the kind of prose randomly selected with consideration of the stories are chosen that contain motifs that are universal or motives that at least has been recorded in a motif index version of Thomson and the estimated contained in oral literature outside Sunda so the motifs found can be used as a comparison of motifs to seek their kinship. The results showed that in the oral literature of Sunda found several motifs such as the origin of the first humans on earth, the origin of the rice, the origin place, the angel who married to a man, man to stone, and the human half of which are universal motifs.Keywords: oral literature Sunda, motifs, and motif-indexAbstrakKeragaman dan kesamaan motif sastra lisan Nusantara sesungguhnya dapat menjadi perekat disintergrasi bangsa serta memperkuat NKRI. Isu-isu tentang kewilayahan, seperti kemelayuan dan otonomi daerah merupakan salah satu “ancaman” perpecahan bangsa ini. Penelitian ini bertujuan mendeskripsikan motif sastra lisan Sunda (sebagai data awal untuk dibandingkan dengan motif sastra lisan daerah lain) yang dapat dimanfaatkan sebagai media jejaring motif untuk penguatan NKRI. Penganalisisan data dilakukan dengan pendekatan motif indeks. Sumber data yang digunakan adalah sastra lisan Sunda jenis prosa yang dipilih secara acak dengan pertimbangan cerita-cerita yang dipilih yang mengandung motif yang bersifat universal atau motif-motif yang minimal sudah tercatat dalam motif indeks versi Thomson serta yang diperkirakan terdapat dalam sastra lisan di luar Sunda sehingga motif yang ditemukan dapat dijadikan bahan perbandingan motif untuk mencari kekerabatannya. Hasil penelitian menunjukkan bahwa di dalam sastra lisan Sunda ditemukan beberapa motif seperti asal-usul manusia pertama di bumi, asal-usul padi, asal-usul tempat, bidadari yang menikah dengan manusia, manusia menjadi batu, dan manusia separuh yang merupakan motif-motif universal.Kata kunci: sastra lisan Sunda, motif, dan motif-indeks